DOMESTIC WORKERS STRUGGLE FOR RECOGNITION AND REDISTRIBUTION IN THE AGE OF CANNIBAL CAPITALISM - Syahwal (Mimbar Hukum, 2024)
Abstract This study stems from the phenomenon of social movements advocating for the legitimacy of the Domestic Workers Protection Bill. It questions the state's ability to fulfill the demands of such social movements. Employing a socio-legal approach, this study utilizes the concept of cannibalistic capitalism and Nancy Fraser’s dualism perspective. This study reveals that the domestic workers' social movement demands both recognition and redistribution through the enactment of the proposed bill. However, Indonesia's legislative paradigm does not allow the state to provide both recognition and redistribution to domestic workers through the law. At best, the state might offer recognition, however redistribution remains unlikely. Abstrak Studi ini berangkat dari fenomena gerakan sosial yang mendorong legitimasi Rancangan Undang-Undang Perlindungan Pekerja Rumah Tangga. Studi ini mempertanyakan kemungkinan negara untuk memenuhi tuntutan gerakan sosial tersebut. Digalang secara sosio-legal, studi ini mendayagunakan formulasi kapitalisme kanibal dan perspektif dualisme dari Nancy Fraser. Studi ini mengungkap bahwa gerakan sosial pekerja rumah tangga menuntut adanya rekognisi dan redistribusi melalui pengesahan rancangan undang-undang yang dimaksud. Akan tetapi, paradigma pembentukan hukum di Indonesia tidak memungkinkan negara untuk memberi rekognisi dan redistribusi kepada pekerja rumah tangga melalui hukum. Paling mungkin, negara hanya akan memberikan rekognisi, tetapi tidak dalam memberikan redistribusi.